The Influence of Individual, Brand, and Corporate Personality on Motorbike Brand Preference - Rani Adhari; Raeni Dwi Santy (Master of Management Department, Faculty of Economics, Universitas Bangka Belitung, 2023)
This research investigates the impact of individual, brand, and corporate personalities on brand preference among motorbike riders. Using a quantitative approach, descriptive and verificative research methods were employed to address the research problem, focusing on individual, brand, and corporate personalities’ influence on brand preference individually and collectively. Primary data were collected through questionnaires distributed to a sample of 100 members of the Aerox Bandung community. The PLS-SEM method, implemented with smartPLS 4 software, was used for data analysis, incorporating primary and secondary data sources. Results indicate that individual, brand, and corporate personalities exert both individual and collective influence on brand preference. This research contributes to marketers’ understanding of the varying degrees of influence that individual, brand, and corporate personalities hold over brand preference. Strengthening these personalities presents opportunities for creating distinctiveness and positively impacting brand preference.